Exchange Transfusion: Indication and Adverse Effect - Begum, Suraiya; Baki, Md Abdul; Kundu, Gopen; Islam, Imnul; Talukdar, Manik Kumar; Fatema, Kaniz (Bangladesh Journal of Child Health, 2012)
Objective: To determine the indication and complications of exchange transfusion (ET) performed for neonatal hyperbilirubinaemia. Methods: The medical records of infants < 28 days old who required exchange transfusion (ET) due to neonatal jaundice in Special Care Baby Unit (SCABU), BIRDEM hospital from January 2009 to April 2010 were retrospectively reviewed. Results: Exchange transfusion was performed in 30 neonates during the study period. Indications of exchange transfusion were ABO incompatibility (30.0%), Rh incompatibility (13.3%), septicaemia (6.6%) and in majority causes, were unidentified (50%). Most common complication were thrombocytopenia (33.3%) hyperkalaemia (20%), hypocalcaemia (16.7%) Conclusion: Indication of ET was unidentified in majority cases and among identified cases most common causes was ABO incompatibility. Adverse events were common after exchange transfusion. DOI: http://dx.doi.org/10.3329/bjch.v36i1.13029 Bangladesh J Child Health 2012; Vol 36 (1): 16-19